Modifikasi Pati Sagu dengan Memanfaatkan Lactobacillus plantarum 1 yang diisolasi dari Industri Pengolahan Pati Sagu - Mikael Franyose Pinem; Yusmarini Yusmarini; Usman Pato (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Modified sago starch (mosas) is sago starch wich has been microbiologically modified by latic acid bacteria. The purposes of this study were to modify the sago starch by microbiologicaly method using Lactobacillus plantarum 1 isolated from sago starch processing industry and to analyze the characteristic of physico chemical properties of modified sago starch. This study was conducted using a Completely Randomized Design (CRD) with three treatments consisting of P0 (L. plantarum 1 RN2-12112 : L. plantarum 1 RN2-53 (1:1)), P1 (L. Plantarum 1 RN2-12112 : L. plantarum 1 RN1-23121 (1:1)), P2 (L. plantarum 1 RN2-53 : L. plantarum 1 RN1-23121 (1:1)). Each treatment were repeated 6 times. The results show that a combination of bacteria in the fermentation significantly affected the swelling power and solubility but did not significantly influence the moisture, ash and crude fiber content as well as the degree of acidity.Keyword: sago starch, modification, Lactobacillus plantarum 1, microbiological method